(untitled) (CAHIERS MAGELLANES-NS, 2024)
In this article, we analyze the manifestations of authorial posture in creative tales written by intermediate-level Moroccan learners. We attempt to examine the impact of creative storytelling on the development of students' autonomy and their sociocognitive, linguistic, and psychological skills. By adopting a pedagogical approach and utilizing theories of writing learning, we analyzed two tales created in French by Moroccan students within the educational program Sabak Al Hikaya. To identify and analyze these manifestations, we used six writing criteria: ideas, organization, voice, word choice, sentence fluency, linguistic norms, and presentation. The qualitative analysis of these manifestations demonstrated that during writing, learners were able to shift their posture from writer, listener, and reader to that of an author. They developed an original and creative style. The messages conveyed were rich in ideas, clear, and relevant. The narration was progressive and fluid. The chosen words and lexical fields employed reinforced the treatment of the announced themes and developed the tone of each text. Variations in sentence length and modality maintained a rhythmic balance in the narratives. Finally, the narrative details, transitions between narrative stages, and the logical sequence of events imparted a coherent and cohesive character to the two tales.